COMPARISON OF IMMUNOHISTOCHEMICAL MARKER WITH SPECIAL STAINS IN THE PROGNOSIS OF THE DIFFERENT GRADES OF ORAL SQUAMOUS CELL CARCINOMA - Nallaiyan, Dr. Parthiban; Ramakrishnan, Dr. Bharathi; Santigo, Dr. Gnanadeepam; Jeyasivanesan, Dr. Dhanalakshmi (Journal of Biomedical and Pharmaceutical Research, 2019)
Objectives: The aim of the study is to compare the efficiency of Ki-67 with special stains in the stroma of different grades of Oral Squamous Cell Carcinoma (OSCC) and to evaluate the influence of these changes in predicting the prognosis of these tumors. Materials and Methods: A total of 30 cases of different grades of Oral Squamous Cell Carcinoma and 6 cases of control were sections and stained with Picrosirus red (PR), combined Alcian blue-periodic acid Schiff reagent (AB-PAS) and Immunohistochemical (IHC) marker Ki-67. Results: Collagen fibre nature using PR stain and proliferative activity of malignant epithelial cells using IHC marker Ki-67 was found to be statistically significant. Mucin presence using AB-PAS was statistically insignificant. Conclusion: Prognosis in different grades of oral squamous cell carcinoma can be accessed by change in collagen fibres birefringence, as the tumour progresses there is change from mature to immature collagen. Ki-67 is a good proliferative marker and shows that there is positive correlation with histological grading of oral squamous cell carcinoma. Presence of acidic or neutral mucin in OSCC needed to be further studied. For assessing the prognosis in different grades of OSCC, special stains can also be used. Keywords: Collagen, Mucin, Squamous cell carcinoma, Ki-67.